How Social Media Marketing Shapes Brand Personality: Evidence from Users of Gojek Super-App Platform - Boby Putra Pratama (STIE AMKOP, 2026)
This study investigates the effect of social media marketing on brand personality in the context of Gojek in Indonesia. The objective of this research is to examine how the dimensions of social media marketing communication, content, characteristics, security, and reputation influence consumers’ perceptions of brand personality. A quantitative research design was adopted using a survey method. Data were collected from Gojek users in Indonesia and analyzed using multiple linear regression to assess the relationships among the variables. The results indicate that social media marketing has a significant simultaneous effect on brand personality. However, at the individual level, only the characteristics dimension demonstrates a statistically significant effect, whereas communication, content, security, and reputation are not significant. These findings suggest that the formation of brand personality in digital platforms is more strongly shaped by perceived brand characteristics than by broader social media marketing activities. In conclusion, this study contributes to the digital branding literature by evidencing the limited explanatory power of social media marketing dimensions. Future research is encouraged to develop more robust and formative measurement models and to incorporate additional variables to better explain brand personality formation in digital contexts. Keywords: Digital Marketing, Social Media Marketing, Brand Personality.